STRATEGI PENGEMBANGAN OBJEK WISATA BUNTU BURAKE DENGAN PENDEKATAN PORTER’S DIAMOND MODEL DI KABUPATEN TANA TORAJA - Londongallo, Megawaty; Natalia Paranoan; Naomi Patiung; Agustinus; Sarah; Kezia Angriani Nura (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2024)
So far, the tourism sector's contribution to PAD in Tana Toraja Regency is minimal, even though Toraja is one of the tourist destinations in Indonesia. The decline in tourist arrivals to Tana Toraja in recent years, among other things, apart from the COVID-19 pandemic in 2020-2022, is also the inability of the Tana Toraja Regency government to meet the needs of tourists. The government's role is not yet optimal, and the condition of tourist objects that are not appropriately handled has become the leading cause of the decline in tourist visits. Various strategies have been implemented, but the results are ineffective,  which impacts the tourism sector's low contribution to Regional Original Revenue. This study aims to analyze the strategy for developing the Buntu Burake Tourism Object using the Porter's Diamond Model approach, which will increase the Tourism sector's contribution to PAD. The method used is qualitative and analyzed using Porter's Diamond Model. Informants who will be interviewed in depth are employees from the Department of Tourism, Youth and Sports, tourism industry managers, traders, travel owners, cleaners, and tourists visiting Tana Toraja. The results of this study show that the Buntu Burake tourism development strategy is quite good, but it needs further strategic development so that tourists will increase. This research is expected to benefit academics and the government, especially the Department of Tourism, Youth and Sports, as it relates to developing the tourism industry using Porter's Diamond Model approach to increase the PAD of Tana Toraja Regency.